(untitled) (Research, Society and Development, 2022)
The assurance of adequate and healthy food involves educational practices that favor inclusion and social justice. Through the access to quality food, populations can achieve better health results, a factor that matches with global health and humanitarian principles. Thus, thinking about apoderamento – a term that differs from empowerment – for food and nutrition, through the articulation between knowledge of Education, Health and food, becomes topics of great importance for the most diverse contexts. Therefore, the focus of this paper is to highlight the possibility of investing in food and nutrition apoderamento, as a human right that can be strengthened and enhanced through Food and Nutrition Education, from the perspective of discussions of health education. For this, a bibliographic and documental survey is used as a basis for the proposed discussion. It is understood, after such movements, that there are great limitations in the scope of food apoderamento, especially to the deterioration of public policies in the face of economic discourses. However, there are good possibilities for implementing ideas and actions on the subject that can help populations.